The cocoa mirid (Hemiptera: Miridae) problem: evidence to support new recommendations on the timing of insecticide application on cocoa in Ghana. (4th February 2014) - Adu-Acheampong, Richard; Jiggins, Janice; van Huis, Arnold; Cudjoe, Anthony Richmond; Johnson, Victress; Sakyi-Dawson, Owuraku; Ofori-Frimpong, Kwasi; Osei-Fosu, Paul; Tei-Quartey, Ebenezer; Jonfia-Essien, William; Owusu-Manu, Michael; Nana Karikari Addo, Maxwell Samuel; et al.
<x content-type="archive" xml:space="preserve">Abstract</x> The government's cocoa spraying gangs in Ghana treat about two million hectares of the crop against black pod disease and mirids, the key insect pests of cocoa in West Africa, each August through to December, based on recommendations issued in the 1950s. A few cocoa farmers use additional pesticides. We studied the temporal distribution of two important mirid species, Distantiella theobroma (Dist.) and Sahlbergella singularis Hagl., in 1991, 1999, 2003 and 2012 to determine the appropriate timing for the application of control measures in current farming systems. There was a significant correlation between mirid abundance and pod availability on trees, as well as the number of basal shoots and the cocoa variety grown. Mirid populations peaked between January and April and from September to October. Surveys (interviews and focus group discussions involving over 300 farmers in 33 cocoa-growing districts) on pesticide use, sources of recommendations, and perceived successes and failures of current cocoa pest treatments suggested that the 1950 recommendations on the timing of insecticide application need revising.